2017
DOI: 10.1111/jssr.12364
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Struggles and Health: Assessing the Influence of Socioeconomic Status

Abstract: Growing evidence suggests that spiritual struggles may play a major role in explaining the relationship between religion and health. Even so, there are significant gaps in the literature. More specifically, researchers do not know enough about how spiritual struggles arise in the first place. This study has two major goals. The first is to see whether socioeconomic status is associated with spiritual struggles. The second is to see whether spiritual struggles are associated with physical health. A conceptual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
1
20
0
4
Order By: Relevance
“…Some research has shown that religious struggles-of which a decrease in religious attendance might be the outward expression-may harm mental health (Hill et al 2017). Religious doubt is known to have a stronger association with various aspects of well-being (e.g., self-esteem, life satisfaction) among the less educated (Krause, Pargament, and Ironson 2017). A precipitous drop in religious attendance could pose a significant mental health threat for the less educated.…”
Section: The Education Contingent Effects Of Religious Transitions For Depressionmentioning
confidence: 99%
“…Some research has shown that religious struggles-of which a decrease in religious attendance might be the outward expression-may harm mental health (Hill et al 2017). Religious doubt is known to have a stronger association with various aspects of well-being (e.g., self-esteem, life satisfaction) among the less educated (Krause, Pargament, and Ironson 2017). A precipitous drop in religious attendance could pose a significant mental health threat for the less educated.…”
Section: The Education Contingent Effects Of Religious Transitions For Depressionmentioning
confidence: 99%
“…Ada keterkaitan antara pendidikan terakhir, pekerjaan dan pendapatan. Pendidikan terakhir menentukan seseorang mendapatkan pekerjaan dan pekerjaan menentukan besaran pendapatan (Krause et al, 2017).…”
Section: Pembahasanunclassified
“…Petuah-petuah agama dan pesan-pesan normative tidak lagi dipedulikan, yang penting kebutuhan dapat terpenuhi tanpa memikirkan dari mana jalan mendapatkannya (Mukti et al, 2019). Sulit meyakini bahwa Tuhan Maha baik, karena minimnya sumber daya spiritual, ada keengganan untuk melakukan koping strategi spiritual (Krause et al, 2017).…”
Section: Pembahasanunclassified
“…Kurang kepercayaan terhadap orang lain, menganggap masalah harus diselesaikan secara mandiri dan takut untuk menyusahkan orang lain, serta menanggap dirinya lemah jika menceritakan suatu masalah pada orang lain juga merupakan beberapa faktor penyebab orang dengan resiko perilaku bunuh diri (Dadašev, Skruibis, Gailienė, Latakienė, & Grižas, 2016). Pada individu tertentu biasanya juga kerap menganggap bahwa masalah yang mereka dapatkan merupakan tanda bahwa mereka merasa ditinggal oleh Tuhan, merasa dihukum, merasa bahwa orang lain tidak menghormati keyakinan agamanya, seringkali menghubungkan suatu masalah dengan peristiwa gaib yang ada hubungannya dengan setan, serta seringkali tidak mampu menemukan makna dalam hidupnya (Krause, Pargament, & Ironson, 2017). Pada orang tua dewasa, kesulitan keuangan, keterbatasan fungsional, depresi, kekurangan fisik pada anak-anak, masalah dalam sosial, kesepian, dan tempat tinggal perkotaan secara signifikan terkait dengan pemikiran bunuh diri (H. Li, Xu, & Chi, 2016).…”
Section: Faktor-faktor Yang Menyebabkan Ide Bunuh Diriunclassified
“…Dukungan agama dapat diberikan dengan didasari oleh individu yang cenderung menganggap bahwa sebuah masalah yang datang padanya merupakan tanda bahwa mereka merasa ditinggal oleh Tuhan, merasa dihukum, merasa bahwa orang lain tidak menghormati keyakinan agamanya, seringkali pula mereka menghubungkan suatu masalah dengan peristiwa gaib yang ada hubungannya dengan setan, serta tidak mampu menemukan makna dalam hidup (Krause et al, 2017). Mencegah resiko perilaku bunuh diri tersebut perlu dilakukan agar gangguan kejiwaan seperti halnya depresi juga dapat diturunkan.…”
Section: Kesimpulanunclassified